Application of Agricultural Extension Principles to Sustainable Agricultural Practices in Rural Communities of Enugu State, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
This paper explored agricultural extension principles that can be applied to sustainable agricultural practices in rural communities of Enugu State, Nigeria. The paper was based on a desk review of available relevant literature. Information was accessed through a web search, Google scholar, open-accessed journals, magazines, periodicals, newspapers, books, and reports. The paper identified sustainable agricultural practices such as ridging/mound making, planting of trees/grasses, terracing, and local water harvesting and examined agricultural extension principles that can be applied to them namely: the principle of starting at the level of farmers, the principle of education of farmers, the principle of cooperative work and principle of constant evaluation. Also, the following challenges were described: inadequate number of extension personnel, poor farmer-extension-research interaction, and low level of education between extension agents and farmers. The paper concluded that agricultural extension principles can be applied to sustainable agricultural practices and recommended recruitment of more educated extension personnel to close the huge gap between extension farmer ratio in the state and constant training of extension workers.
Keywords: Agricultual practices; Enugu State; Extension; Principle; Sustainable agriculture